-Seeking Blessings and Manifestations of Deviation - Common Deviations of Muslims in Albania: A Case Study - Pasha, Susanna Rajab (Journal of Humanities & Social Sciences, 2018)
One of the most important creed issues that have spread among Muslims is that of the subject of perversity. There is no doubt that perversity is two types, one is legitimate as it is allowed by the proof of the Holy texts; and the other is forbidden by proof of holy texts as well. The perversity may relate to time, place, persons or other things, and the deviations are evident in this section, so some Muslims are doing everything they think is righteous and blessed with the possibility, the times and the good to wipe and touch and so on. In this research, I have stated the position of the Shariah on all this and what the Muslim must have, and I have allocated part of my study to show deviations in the perversity at and remedies for the Muslims of Albania, one of the most important reasons for these deviations has been found to be the ignorance of religion and its provisions, and to be influenced by the old pagans that It was common before Islam and the spread of misguided contraptions and sects among Muslims.
Keywords: deviation; Albania; blessing; graves; places; people; shrines